Development and Implementation of Continuing Vocational Pedagogic Education - G. N. Zhukov (Russian State Vocational Pedagogical University, 2015)
The paper is devoted to organizing and ensuring the effectiveness of continuing vocational education. The author describes the general theoretical idea of a lifelong education that no longer raises any doubts and objections. The continuing education is regarded as a versatile process affecting psychological, social and professional spheres, and requiring therefore the integrative - i. e. personal, social and competence approach.Referring to the expertise of Kemerovo region, the author considers the functional aspects of continuing vocational teacher training. The main emphasis is on the advantages of the network cooperation of institutions representing different educational levels and structures. Such cooperation involves the qualitative changes of content, as well as economics and management of vocational education. The experimental project of the network lead-up for vocational training masters is described.